The reliability and validity of the Timed Up and Go test in patients ongoing or following lumbar spine surgery: a systematic review and meta-analysis - Fatih Özden (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2024)
Abstract Background No other systematic review examined the measurement properties of the TUG in LSS. The present systematic review and meta-analysis aimed to investigate the measurement properties of the Timed Up and Go (TUG) in patients with Lumbar Spine Surgery (LSS). A literature search yielded 906 studies [PubMed:71, Web of Science (WoS):80, Scopus:214, ScienceDirect:471 and Cochrane Library:70]. Included 10 studies were assessed for risk of bias and quality using the “four-point COSMIN tool” and “COSMIN quality criteria tool”. Criterion validity and responsiveness results were pooled with “correlation coefficient” and “Hedges’ g” based effect size, respectively. Results The correlation coefficient pooling between TUG and VAS back and leg pain was 0.26 (moderate) (95% CI 0.19–0.34) and 0.28 (moderate) (95% CI 0.20–0.36). The pooled coefficient of TUG with ODI and RMDI was 0.33 (moderate) (95% CI 0.27–0.39) and 0.33 (moderate) (95% CI 0.24–0.42), respectively. Besides, TUG has correlated with the quality-of-life PROMs with a coefficient of − 0.22 to − 0.26 (moderate) (EQ5D Index 95% CI − 0.35 to − 0.16), (SF12-PCS 95% CI − 0.33 to − 0.15) and (SF12-MCS 95% CI − 0.32 to − 0.13). The pooled coefficient of TUG with COMI, ZCQ-PF and ZCQ-SS was 0.46 (moderate) (95% CI 0.30–0.59), 0.43 (moderate) (95% CI 0.26–0.56), and 0.38 (moderate) (95% CI 0.21–0.52), respectively. TUG’s 3-day and 6-week responsiveness results were 0.14 (low) (95% CI − 0.02 to 0.29) and 0.74 (moderate to strong) (95% CI 0.60–0.89), respectively. TUG was responsive at the mid-term (6 weeks) follow-up. Conclusion In clinical practice, the TUG can be used as a reliable, valid and responsive tool to assess LSS patients’ general status, especially in mid-term.